Proceedings of the 11th International Conference on Product Focused Software 2010
DOI: 10.1145/1961258.1961292
|View full text |Cite
|
Sign up to set email alerts
|

Core handover problems

Abstract: Even if a handover process is a critical stage in the software lifecycle, little is known about the problems encountered when transferring a software system from development to maintenance. In this paper, we have elicited five core handover problems as faced by five IT organizations today. These are (1) insufficient system knowledge, (2) lack of domain knowledge, (3) insufficient communication, (4) inadequate documentation, and (5) difficulties in tracking changes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…However, the real complexity and its industrial relevance can be revealed only when the taxonomy is matched against industrial handover processes. It is evident from [3] that organizations face critical problems during system handover. These problems concern system knowledge, domain knowledge, communication gap between participating parties, documentation, and tracking system changes.…”
Section: Final Remarks and Future Workmentioning
confidence: 99%
“…However, the real complexity and its industrial relevance can be revealed only when the taxonomy is matched against industrial handover processes. It is evident from [3] that organizations face critical problems during system handover. These problems concern system knowledge, domain knowledge, communication gap between participating parties, documentation, and tracking system changes.…”
Section: Final Remarks and Future Workmentioning
confidence: 99%